Mental and physical health correlates of the psychological impact of the first wave of COVID-19 among general population of Pakistan - Kazmi, Syed Messum Ali; Lewis, Christopher Alan; Hasan, Syeda Salma; Iftikhar, Rabia; Fayyaz, Muhammad Umar; Anjum, Fayyaz Ahmed (Frontiers in Psychology, 2022)
The primary aim was to assess the role of mental and physical health of the psychological impact of COVID-19 on the general population of Pakistan during the first wave of COVID-19. It was hypothesized that there would be a significant predictive association among socio-demographic variables, psychological impact and mental health status resulting from COVID-19, and poor self-reported physical health would be significantly associated with adverse psychological impact and poor mental health status because of COVID-19. A cross-sectional survey research design was used in which 1361 respondents were sampled online during lockdown imposed in the country. The Impact of Events Scale-Revised (IES-R) was used to assess the psychological impact of COVID-19, and the Depression, Anxiety and Stress Scale (DASS-21) was used to assess participants’ mental health status. 18 % of the respondents reported moderate to severe event-specific distress, 22.6 % reported moderate to severely extreme depression, 29 % reported moderate to extreme anxiety, and 12.1 % reported moderate to extreme stress. Female gender, having graduate-level education, currently studying, and self-reported physical symptoms (persistent fever, chills, headache, cough, breathing difficulty, dizziness, and sore throat) were significantly associated with higher levels of psychological impact exhibited through higher scores on the IES-R and poorer mental health status exhibited through higher scores on the DASS-21 (depression, anxiety, and stress subscales).